Exonic WT1 pathogenic variants in 46, XY DSD associated with gonadoblastoma. Issue 12 (25th November 2021) - Arya, Sneha; Kumar, Sandeep; Lila, Anurag R; Sarathi, Vijaya; Memon, Saba Samad; Barnabas, Rohit; Thakkar, Hemangini; Patil, Virendra A; Shah, Nalini S; Bandgar, Tushar R
Abstract : Objective: The literature regarding gonadoblastoma risk in exonic Wilms' tumor suppressor gene ( WT1) pathogenic variants is sparse. The aim of this study is to describe the phenotypic and genotypic characteristics of Asian–Indian patients with WT1 pathogenic variants and systematically review the literature on association of exonic WT1 pathogenic variants and gonadoblastoma. Design: Combined retrospective–prospective analysis. Methods: In this study, 46, XY DSD patients with WT1 pathogenic variants detected by clinical exome sequencing from a cohort of 150 index patients and their affected relatives were included. The PubMed database was searched for the literature on gonadoblastoma with exonic WT1 pathogenic variants. Results: The prevalence of WT1 pathogenic variants among 46, XY DSD index patients was 2.7% (4/150). All the four patients had atypical genitalia and cryptorchidism. None of them had Wilms' tumor till the last follow-up, whereas one patient had late-onset nephropathy. 11p13 deletion was present in one patient with aniridia. The family with p.Arg458Gln pathogenic variant had varied phenotypic spectrum of Frasier syndrome; two siblings had gonadoblastoma, one of them had growing teratoma syndrome (first to report with WT1). On literature review, of >100 exonic point pathogenic variants, only eight variants (p.Arg462Trp, p.Tyr177*, p.Arg434His, p.Met410Arg, p.Gln142*, p.Glu437Lys, p.Arg458*, and p.Arg458Gln) in WT1 were associated with gonadoblastoma in a total of 15 cases (including our two cases). Conclusions: WT1 alterations account for 3% of 46, XY DSD patients in our cohort. 46, XY DSD patients harboring exonic WT1 pathogenic variants carry a small but definitive risk of gonadoblastoma; hence, these patients require a gonadoblastoma surveillance with a more stringent surveillance in those harboring a gonadoblastoma-associated variant.